Impaired vascular β-adrenergic relaxation in spontaneously hypertensive rats: The differences between conduit and resistance arteries - Valovič, Pavol; Behuliak, Michal; Vaněčková, Ivana; Zicha, Josef (European journal of pharmacology, 2023)
It was suggested that impaired β-adrenergic relaxation in spontaneously hypertensive rats (SHR) might contribute to their high blood pressure (BP). Our study was focused on isoprenaline-induced dilatation of conduit femoral or resistance mesenteric arteries and on isoprenaline-induced BP reduction in SHR and Wistar-Kyoto rats (WKY). We confirmed decreased β-adrenergic relaxation of SHR femoral arteries due to the absence of its endothelium-independent component, whereas endothelium-dependent component of β-adrenergic smooth muscle relaxation was similar in both strains. Conversely, isoprenaline-induced relaxation of resistance mesenteric arteries was similar in both strains and this was true for endothelium-dependent and endothelium-independent components. We observed moderately reduced sensitivity of SHR mesenteric arteries to salmeterol (β2-adrenergic agonist) and this strain difference disappeared after endothelium removal. However, there was no difference in mesenteric arteries relaxation by dobutamine (β1-adrenergic agonist) which was independent of endothelium. The increasing isoprenaline doses elicited similar BP decrease in both rat strains, although BP sensitivity to isoprenaline was slightly decreased in SHR. The blockade of cyclooxygenase (indomethacin) and NO synthase (L-NAME) further reduced BP sensitivity to isoprenaline in SHR. On the other hand, salmeterol elicited similar BP decrease in both strains and the blockade of cyclooxygenase and NO synthase increased BP sensitivity to salmeterol in SHR as compared to WKY. In conclusion, attenuated β-adrenergic vasodilatation of conduit arteries of SHR but similar β-adrenergic relaxation of resistance mesenteric arteries from WKY and SHR and their similar BP response to β-adrenergic agonists do not support major role of altered β-adrenergic vasodilatation for high BP in genetic hypertension.
Keywords: Mesenteric Arteries; Isoproterenol; potkani inbrední WKY; agonisté adrenergních beta-receptorů; Prostaglandin-Endoperoxide Synthases; hypertenze; cévní endotel; Resistance mesenteric artery; cévní rezistence; β(2)-agonist salmeterol; potkani inbrední SHR; adrenergní látky; Isoprenaline; Endothelium, Vascular; Hypertension; cyklooxygenasy; arteriae mesentericae; krysa rodu Rattus; Salmeterol Xinafoate; Adrenergic Agents; Animals; β(1)-agonist dobutamine; Vascular Resistance; zvířata; Nitric Oxide Synthase; synthasa oxidu dusnatého; Rats; isoprenalin; salmeterol xinafoát; Rats, Inbred SHR; Blood pressure; Rats, Inbred WKY; Femoral artery; Adrenergic beta-Agonists